Development of settlement arrangements in civil legal proceedings - Sadykova, K.K.; Batyrbayeva , Zh.K. (Bulletin of the Karaganda University “Law Series”, 2019)
The article is devoted to the analysis of the current legislation and judicial practice of the application of settlement arrangements in the civil legal proceedings, as well as the development of proposals for their development. The article gives a description of the types of settlement arrangements provided for by national civil procedural legislation, analyzes the judicial practice of applying settlement arrangements in civil proceedings and develops proposals to improve the institution of settlement arrangements. The advantage of settlement arrangements for the court is a significant reduction in the load, since it increases from year to year, which may affect the quality of decisions and the execution of judicialacts. However, this factor cannot be recognized as the primary reason for helping the parties to reconcile, since the elimination of the conflict and dispute between them should be a priority in reducing the number of civil cases that require a trial and a decision. In addition, the article presents the results of a study ofthe dynamics of the development of the application of settlement arrangements over the past three years, taking into account the prevailing judicial practice to determine the growth trend of disputes settled by peaceful means, the level of distribution and popularization among the population.